Calouste Gulbenkian Museum - Pimentel, António Filipe (Scala Arts & Heritage Publishers, 2023)
The Museu Calouste Gulbenkian's houses one of the world's most important private art collections, comprising artworks assembled by Calouste Sarkis Gulbenkian and ranging from Egyptian, Greco-Roman and Mesopotamian art to painting, sculpture and the decorative arts. In this addition to the successful Director's Choice series, Antonio Filipe Pimentel, who has been the Director of the Calouste Gulbenkian Museum since January 2021, showcases a range of spectacular pieces, summarising the Museum's treasures in a beautifully illustrated guide
Keywords: Museu Calouste Gulbenkian; Kunst; Sammlung; Katalog; Bildband